Priority Development of Dairy Farming Business to Support Government Policies in The Special Region of Yogyakarta And Central Java - Gielbran Muhammad Noor; Abidah Thorifatus Alya; Ahmad Romadhoni Surya Putra (Agrisocionomics: Jurnal Sosial Ekonomi Pertanian, 2025)
The implementation of government policies that align with the need to increase dairy productivity in Indonesia is crucial. Ensuring policy compatibility with the dairy sector's needs requires setting priorities through a direct, participatory, and bottom-up approach involving dairy sector stakeholders. This study aims to identify priority development programs for dairy farming businesses within the framework of government policies that align with the real needs of dairy sector stakeholders. A quantitative approach was used, employing the Analytical Hierarchy Process (AHP) pairwise comparison method. Dairy productivity was set as the main goal, assessed through three key criteria: capital, dairy farming infrastructure, and the quality of human resources. The evaluated alternatives included the use of information technology, livestock seed grants, mentoring, institutional support, government policies, and supply chain improvements. Data were collected via questionnaires from seven key informants representing dairy farmers, policymakers from the Department of Agriculture, Food, and Fisheries, Sleman Regency, non-governmental organizations (NGOs), dairy farmer associations, academics, researchers, and the dairy processing industry. The research was conducted in the Special Region of Yogyakarta and Central Java Province in August 2024. The findings indicate that mentoring is the most prioritized government policy program among dairy farmers, with a relative weight of 0.242. Additionally, the quality of human resources emerged as the most critical criterion for dairy sector stakeholders, with a relative weight of 1.000. These results highlight that improving the quality and education level of human resources in the dairy sector is a key factor in enhancing dairy productivity. The findings suggest that government programs should focus more on long term, farmer centered mentoring strategies, supported by consistent policy implementation, qualified facilitators, and collaboration with cooperatives and educational institutions to ensure sustainable dairy sector development.